2023
DOI: 10.3390/children10050785
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Gait Impairments in Children with Clubfeet Treated by the Ponseti Method: A Systematic Review and Meta-Analysis

Abstract: Background: Being aware of possible gait impairments in Ponseti-treated clubfoot children might be useful for optimizing initial and additional treatment. Therefore, this systematic review and meta-analysis aimed to identify kinematic gait abnormalities in children with clubfoot treated with the Ponseti method (with and without relapse). Methods: A systematic search was conducted. Studies comparing kinematic gait parameters of Ponseti-treated clubfoot children to healthy controls were included. Meta-analyses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(278 reference statements)
0
1
0
Order By: Relevance
“…Los pacientes del presente estudio por el promedio de edad que tenían abandonaron el tratamiento muy precozmente. Esta situación se asocia a una mayor dificultad en el manejo futuro, mayores posibilidades del tratamiento quirúrgico y secuelas como los trastornos en la marcha, rigidez (15)(16)(17) del pie entre otros .…”
Section: Discussionunclassified
“…Los pacientes del presente estudio por el promedio de edad que tenían abandonaron el tratamiento muy precozmente. Esta situación se asocia a una mayor dificultad en el manejo futuro, mayores posibilidades del tratamiento quirúrgico y secuelas como los trastornos en la marcha, rigidez (15)(16)(17) del pie entre otros .…”
Section: Discussionunclassified
“…The purpose of treating clubfoot is to relieve foot pain, obtain a normal appearance, and restore normal function. At present, the Ponseti method (manipulation, casting, cementing, or an Achilles tenotomy) is considered the gold standard for early treatment ( Ganesan et al, 2017 ; Grin et al, 2023 ). A transplantar pressure study showed that, compared to those of the healthy side and control group, clubfoot treated with the Ponseti method had higher peak pressure (PP) and pressure‒time integral (PTI) in the lateral forefoot and midfoot; moreover, the contact area reported as a percentage of the total foot area (CA%) was also significantly greater, while the PP and PTI were significantly lower in the medial forefoot and hindfoot, suggesting that the affected foot experiences significantly greater mechanical stress during walking and that the load is transferred from the medial side of the foot to the lateral forefoot and midfoot ( Xu et al, 2018 ).…”
Section: Application In Foot and Ankle Diseasesmentioning
confidence: 99%